Nurse's care characteristics of cardiovascular patients - Ariza Olarte, Claudia; Pontificia Universidad Javeriana (Pontificia Universidad Javeriana - Facultad de Enfermería, 2011)
In this article we talk about two issues that although they are different in concept, view and principles, they also combine and are the esence of nurse's work which one out of all is to manage the care: in first place the quality of care and in second, the proposal of nurse's actions that can help to aquick recovery and to wich apply the quality concept.